2020
DOI: 10.1021/acsomega.0c02773
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Basalt Glasses as High-Temperature Sensible Heat Storage Materials

Abstract: Thermal energy storage (TES) systems are a key technology that utilizes renewable energy and low-level thermal energy to ensure continuous and stable operation in concentrated solar power plants, family heating, and industrial waste heat recovery fields. It solves the intermittent problem of solar radiation and significantly improves energy efficiency and economic benefits. Three varieties of natural basalt ores have been selected, namely, intermediate, basic, and ultrabasic basalt, which have been prepared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It has been reported that water, molten salts, and concrete can be used as energy sources when the sensible heat storage technique is used to address the energy problems and mannitol and microcapsulated phase change materials (PCMs) can be used as energy sources when the latent heat storage technique is used to meet the energy demand. [1][2][3][4][5][6][7] The heat storage density and longterm heat storage capacity achieved using the CHS technique was better than the heat storage density and long-term heat storage capacity achieved using the other two techniques. [8][9][10][11][12][13] Therefore, in our previous studies, the CHS technique has received attention for energy conservation.…”
Section: Introductionmentioning
confidence: 87%
“…It has been reported that water, molten salts, and concrete can be used as energy sources when the sensible heat storage technique is used to address the energy problems and mannitol and microcapsulated phase change materials (PCMs) can be used as energy sources when the latent heat storage technique is used to meet the energy demand. [1][2][3][4][5][6][7] The heat storage density and longterm heat storage capacity achieved using the CHS technique was better than the heat storage density and long-term heat storage capacity achieved using the other two techniques. [8][9][10][11][12][13] Therefore, in our previous studies, the CHS technique has received attention for energy conservation.…”
Section: Introductionmentioning
confidence: 87%
“…Consequently, heat storage techniques have gained increasing attention, and the main heat storage techniques nowadays are sensible, latent, and chemical heat storage (CHS) techniques. Water, molten salts, basalt, and concrete have been reported as sensible heat storage materials, whereas mannitol, paraffin, fatty acids, polyethylene glycol, and microcapsule phase-change materials have been used as latent heat storage materials. In addition, the heat storage density and long-term heat storage parameters for the CHS technique are typically better than those for the other two techniques. Therefore, in our previous studies, we focused on the CHS technique, owing to its energy conservation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming and climate change, due to the escalating emission of CO 2 by fossil fuel consumption, are some of the most serious environmental issues that humankind has faced in recent years. , To tackle these challenges, research has focused on the effective and economical use of renewable energy as well as unharnessed thermal energy sources. To exploit the latter, chemical heat storage (CHS) materials have received particular attention because of their high energy storage density and long-term storage period. Recycling systems for heat at high temperatures, such as in chemical plants, power plants, incinerators, etc., are sophisticatedly designed to save total energy consumption using CHS materials .…”
Section: Introductionmentioning
confidence: 99%